Outcomes in Pancreas Transplantation With Exocrine Drainage Through a Duodenoduodenostomy Versus Duodenojejunostomy. Issue 1 (23rd August 2017) - Lindahl, J. P.; Horneland, R.; Nordheim, E.; Hartmann, A.; Aandahl, E. M.; Grzyb, K.; Haugaa, H.; Kjøsen, G.; Åsberg, A.; Jenssen, T.
Abstract : Until recently, pancreas transplantation has mostly been performed with exocrine drainage via duodenojejunostomy (DJ). Since 2012, DJ was substituted with duodenoduodenostomy (DD) in our hospital, allowing endoscopic access for biopsies. This study assessed safety profiles with DD versus DJ procedures and clinical outcomes with the DD technique in pancreas transplantation. DD patients (n   =   117; 62 simultaneous pancreas–kidney [SPKDD ] and 55 pancreas transplantation alone [PTADD ] with median follow‐up 2.2 years) were compared with DJ patients (n   =   179; 167 SPKDJ and 12 PTADJ ) transplanted in the period 1998–2012 (pre‐DD era). Postoperative bleeding and pancreas graft vein thrombosis requiring relaparotomy occurred in 17% and 9% of DD patients versus 10% (p   =   0.077) and 6% (p   =   0.21) in DJ patients, respectively. Pancreas graft rejection rates were still higher in PTADD patients versus SPKDD patients (p   =   0.003). Hazard ratio (HR) for graft loss was 2.25 (95% CI 1.00, 5.05; p   =   0.049) in PTADD versus SPKDD recipients. In conclusion, compared with the DJ procedure, the DD procedure did not reduce postoperative surgical complications requiring relaparatomy or improve clinical outcomes after pancreas transplantation despite serial pancreatic biopsies for rejection surveillance. It remains to be seen whether better rejection monitoring in DD patients translates into improved long‐term pancreas graft survival. Abstract : Pancreas transplantation with exocrine drainage through a duodenoduodenostomy does not reduce postoperative surgical complications or improve pancreas graft survival compared with duodenojejunostomy.